On hierarchical modulation for satellite broadcasting. (19th June 2018) - Kayhan, F.; Montorsi, G.; Taricco, G.; Alagha, N.
Summary: This paper presents a comparative assessment of 2 multiplexing techniques for providing differentiated classes of services over a realistic broadcasting satellite channel under variable link conditions. A distinctive property of satellite broadcasting channels is the nonlinear characteristics of high power amplifier on‐board of the satellite. Hence, the conventional additive white Gaussian noise channel with average power limitation is no longer an accurate model, and nonlinear characteristics have to be taken into account. In this paper, we compare the performance of time division multiplexing techniques combined with variable coding and modulation with that of hierarchical modulations delivering contents with 2 (or more) differentiated service qualities. The goal is to maximize the throughput over a given transponder while maintaining a target service availability. We design a practical transmitter scheme based on the hierarchical modulation and maximize the throughput by optimizing the achievable mutual information for finite size constellations. This optimization is done for additive white Gaussian noise channel with both average and peak power limit and will provide a lower bound on throughput, which can be achieved by nonorthogonal multiplexing scheme. The results indicate that the gains obtained by nonorthogonal multiplexing is significant only if the required signal to noise threshold for 2 services differ by more than 10 dB. Finally, we provide the bit error ratio simulation results for some selected scenarios. Abstract : We compare the performance of time division multiplexing techniques combined with variable coding and modulation with that of hierarchical modulations. The results indicate that the gains obtained by hierarchical modulation are significant when the required signal to noise threshold for 2 services differ by more than 10 dB.